An academician's thought leadership on national transformation success - Han, Chun Kwong (School of Economics, Faculty of Economics and Management, Universiti Kebangsaan Malaysia, 2013)
The Government has been taking a radically new approach to national transformation in the past three years. The Government Transformation Programme was initiated in 2009, followed by the New Economic Model and Economic Transformation Programme in 2010, and subsequently political and rural transformation. The “Transformation Budget 2012” announced the “National Transformation Policy”. Presently, transformation can be perceived as the inception stage, as the various programmes will be undergoing a long continuous implementation journey into 2020. In order to make a real significant change to the country, the transformation needs to be driven from a synthesis of economic, managerial, organizational, social and technological dimensions at the multiple levels of the individual, organization, industry, government, society and nation. We offer another way of seeing and doing transformation using a “theory of everything” based on simplicity and sophistication. The extant national transformation model of “Doing and Being” or Yin Yang is a simplicity model. As Malaysian academicians, we have a significant role to provide thought leadership by combining the “Doing and Being” with a sophisticated model based on an understanding the complexity of human behaviour. We combine the Pemandu’s model with a model of sophistication based on an enhanced framework of critical practice. We define critical practice is an iterative reflexive process, firstly by developing knowledge-for-understanding from a sophisticated model of reality. Secondly, we provide a critique of underpinning assumptions and presumptions whereby the constraining conditions of the status quo and emancipation become knowable and explicit, that is, knowledge-for-evaluation. Thirdly, we re-create, re-define, re-design, re-imagine, re-invent and re-vision the pragmatic, doable and implementable programmes from knowledge-for-action. This theory of everything provides a new vigorous theoretical model to review and redesign the practical methodology for implementation success of the national transformation programmes.